2003
DOI: 10.1046/j.1095-8312.2003.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships between parthenogens and their sexual relatives: the possible routes to parthenogenesis in animals

Abstract: In theory, parthenogenetic lineages have low evolutionary potential because they inexorably accumulate deleterious mutations and do not generate much genotypic diversity. As a result, most parthenogenetic taxa occupy the terminal nodes of phylogenetic trees. The rate and mode of development of parthenogenesis are important factors to consider when assessing its costs and benefits since they determine both the level of genetic diversity and the ecological adaptability of the resulting lineages. The origin of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
479
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(489 citation statements)
references
References 98 publications
8
479
0
2
Order By: Relevance
“…Molecular studies have nevertheless confirmed that the apomictic RKN species share a common lineage, and that they diverged early from meiotic species (Castagnone-Sereno et al, 1993b;Baum et al, 1994). There are several ways in which parthenogenetic lineages could arise (Simon et al, 2003). In the case of RKN, no fossil records are available, and the ancestors of the genus are unknown.…”
Section: Parthenogenesis In Rknmentioning
confidence: 99%
“…Molecular studies have nevertheless confirmed that the apomictic RKN species share a common lineage, and that they diverged early from meiotic species (Castagnone-Sereno et al, 1993b;Baum et al, 1994). There are several ways in which parthenogenetic lineages could arise (Simon et al, 2003). In the case of RKN, no fossil records are available, and the ancestors of the genus are unknown.…”
Section: Parthenogenesis In Rknmentioning
confidence: 99%
“…Hybridization may have occurred both in nature and in the aquarium. Parthenogenesis of a contagious origin, that is the hybridization of females from a pre-existing parthenogenetic lineage with males of either the same or a closely related species, is common in brine shrimp and ostracods and generally results in polyploid unisexuals (Simon et al, 2003). The critically endangered hairy marron, Cherax tenuimanus, an endemic species in the Margaret River, Western Australia, is being rapidly replaced by the invasive smooth marron, C. cainii (Bunn et al, 2008).…”
Section: Factors Possibly Affecting the Genesis Of Unusual Reproductimentioning
confidence: 99%
“…Different ways have been described, in which parthenogenetic lineages may originate from sexual species (reviewed in Simon et al, 2003). The majority of the cases of parthenogenesis studied today are associated with bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Such mutations may result in the establishment of an obligate parthenogenetic lineage, or may also initiate a lineage in which a small proportion of females has the potential for parthenogenetic reproduction, which in turn will provide for the possibility to select for parthenogenesis in the laboratory and in nature (Templeton, 1982;Kramer and Templeton, 2001). Spontaneous origins of parthenogenesis have been shown in a wide range of invertebrates, including snails, ostracods, crustaceans and insects (reviewed in Simon et al, 2003). Tychoparthenogenesis refers to the occasional, spontaneous development of eggs without fertilization in otherwise sexually reproducing species, a form of reproduction which is characterized by a low-hatching success of unfertilized eggs (White, 1973;Bell, 1982;Suomalainen et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation